Analysis of Solid-Liquid Interface Behavior during Continuous Strip-Casting Process Using Sharp-Interface Technique - Changbum Lee; Wooyoung Yoon; Seungwon Shin; Jaewoo Lee; Hee-eun Song (International Journal of Photoenergy)
Continuous strip casting (CSC) has been developed to fabricate thin metal plates while simultaneously controlling the microstructure of the product. A numerical analysis to understand the solid-liquid interface behaviors during CSC was carried out and used to identify the solidification morphologies of the plate, which were then used to obtain the optimum process conditions. In this study, we used a modified level contour reconstruction method and the sharp-interface method to modify the interface tracking, and we performed a simulation analysis to identify the differences in the material properties that affect the interface behavior. The effects of the process parameters such as the heat transfer coefficient and extrusion velocity on the behavior of the solid-liquid interface are estimated and also used to improve the CSC process.